[Kusumāñjalikārikā] = Kusumāñjalikārikā of Udayanācārya ; with the commentary Kusumāñjalikārikāvyākhyā of Rāmabhadra Sārvabhauma and Sanskrit notes compiled by Chandidasa Nyaya-Tarkatirtha ; edited by Narendrachandra Vedantatirtha - Udayanācārya (Asutosh Sanskrit series, 1944)
Classical work, with commentary, on Nyaya philosophy.